Fiber optic accelerometer based on grating inscribed over innermost-clad of multi-clad fiber. (August 2018) - Bao, Weijia; Qiao, Xueguang; Rong, Qiangzhou; Wang, Ruohui; Shao, Zhihua; Chen, Fengyi
Highlights: We present a novel fiber Bragg grating inscribed along fiber cross-section of core and innermost depressed-index cladding by femtosecond laser side-illumination technique. The device has a great performance for acceleration measurement with high resolution and orientation dependence. The sensing system is based on simple and cost-effective intensity modulation. The sensor achieves the self-calibration for temperature and power fluctuation. Abstract: A special fiber Bragg grating (FBG) that is inscribed over the core and innermost depressed-index cladding of a short multi-clad fiber (MCLF) by femtosecond laser side-illumination technique is proposed and demonstrated for orientation-dependent measurement, experimentally. Splicing the MCLF with standard single-mode fiber (SMF) provides a cladding-mode generation mechanism via core mismatch, and then "cladding FBG" in MCLF can simultaneously generate two resonances in reflection. The cladding mode shows a significant response to fiber bending due to novel refractive-index profile of MCLF and coupling in the splicing junction. And the asymmetry "cladding FBG" configuration relatively to fiber core center enables it to perform strong orientation-dependent response to the fiber bending. These two properties are well applied to measure acceleration with high resolution of 0.02 m/s 2 and orientation-dependence. The cladding and core mode also present linear wavelength-shifting with temperature variation but no intensity fluctuations. Furthermore, the accidental power perturbation or cross-sensitivity can be calibrated out by monitoring the fundamental core mode resonance.